An Overview of the Entrepreneurial Mentality of Javanese People as Traveling Meatball Vendors - Wahyu Ramadhani; Yeltas Putra , Yanladila; ramadhani, wahyu (Causalita, 2026)
Entrepreneurial mentality refers to the psychological readiness, emotional resilience, and positive attitude possessed by an individual in running and developing a business independently, as demonstrated through courage in taking risks, perseverance, a strong fighting spirit, responsibility, as well as the ability to adapt and innovate amidst challenges and obstacles in the business world. This research focuses on the entrepreneurial mentality of Javanese individuals by involving two mobile meatball vendors as the research subjects. The study employs a qualitative approach with an ethnographic communication method, using the data analysis technique of Miles, Huberman, and Saldana, which consists of three stages: data condensation, data display, and conclusion drawing. Data collection was carried out through in-depth interviews with Javanese mobile meatball vendors. The research identified three categories related to entrepreneurial mentality. The first category, sources of entrepreneurial mentality, includes concepts such as self-will, freedom, self-control, independence, courage, opportunity recognition, learning from experience, and aspiration. The second category, the business being undertaken, includes concepts such as patience, creativity, opportunity reading, self-awareness, self-confidence, perseverance, hard work, and humility. The third category, the application of entrepreneurial mentality, covers concepts such as dealing with competition, maintaining customer trust, strategies to attract customers, preventing losses, customer service, overcoming limited capital, financial calculation in business, managing risks, and resilience.